Hubungan Faktor internal dengan respon pengolah gula aren terhadap teknologi mesin pengolahan modern - Yayah Haeriah; Vega Chendra Mulyana; Asep Najmudin; Edeng Edeng; Wendi Juliawan (University of Insan Cendekia Mandiri, 2025)
The machine for processing sap into ant sugar is a new technology that will be a solution to meet increasing market demand, both in terms of quality and quantity. Age background, education level, experience as a processor and number of ownership as internal factors of the processor will influence their response to the machine technology for processing sap into ant sugar. This research aims to determine the relationship between internal factors and the processor's response to machine technology for processing sap into sugar. The research method used a verification survey, samples were taken from 6 people from 12 people processing sap into palm sugar in Nanggerang Village, Nyalindung Village, Cisewu District, Garut Regency. The results of the research show that the internal factors in the categories of age, level of education, business experience, and cumulative number of sugar palm trees owned are in the medium category. The processor's response is partially seen based on the processor's knowledge indicators which are in the medium category, attitudes are in the high category, experience and implementation are in the low category. The result is a Spearman Rank Correlation Coefficient (rs) of 0.43, meaning that the relationship between Internal Factors consisting of age, level of education, business experience, number of palm trees and the processor's response to the machine processing sap into ant sugar is 43%.